Отандағы нарығындағы жарнама дамуының ерекшеліктерін зерттеу - Tuleuova G.K. Тулеуова Г.К.; Sagimbekova A.M. Сагимбекова А.М. (Рroblems of engineering and professional education, 2022)
The article deals with the development of the domestic advertising market, the formation of advertising, as a type of economic activity. Formed the idea of the state and priority directions of development of individual segments of the advertising market, the changes in the role of advertising in society and the market.